Between art and ritual : An analysis of the performances of Drag Sethlas at the Gran Canaria Drag Queen Contest (2017–20) - Korte, Anne-Marie (Approaching Religion, 2022)
This article analyses the short performances of Drag Sethlas at the yearly Gran Canaria Drag Queen Contest in Spain (2017–20) from the perspective of religious studies and gender studies, following on from an earlier article in which this case was explored in light of the severe blasphemy accusations (by local and national bishops and lay organisations) against the 2017 show. These short performances consist of remarkable representations of Roman Catholic texts, saints, symbols and rituals acted out as prize-winning drag-queen shows that were aired on national television. At the same time, these acts are situated, by reference to famous earlier controversial acts by the pop artists Madonna, Lady Gaga and Ariana Grande, in a genealogy of provocations and blasphemy accusations that are currently made in North American and Western European countries. In exploring the forms of ritualisation (cf. Bell 1989) in the provocation that this type of popular artistic performance with strong religious connotations evokes, I show the presence of a double theatricality in Sethlas’s first and most controversial performance: on the one hand a ‘holy drama’ centred around a religious pattern of penance, repentance and redemption, and on the other hand a specific drag theatricality, with its parodies, mockery and daring erotic scenes. It is precisely the connection between both forms of theatricality, especially the representation of the Virgin Mary and Jesus, who play a large and special role in both forms of theatricality, that contributes most to the provocativeness of this scene.